Post-socialist challenges of a monotown: Eisenhüttenstadt between deindustrialization and rethinking heritage (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
This article examines the trajectories of post-socialist transformation inEisenhüttenstadt between 1990 and 2025 as a planned monocity originally developed around a cityforming enterprise – Steelworks Combine East (Eisenhüttenkombinat Ost). The study analyzes howspatial, institutional, and socio-cultural changes intersect under conditions of deindustrialization,demographic decline, and state-led programs of «managed shrinkage». These processes resulted inlarge-scale demolition of residential buildings, selective concentration of resources in preservedurban cores, and substantial reconfiguration of infrastructural and service systems. Drawing on acombination of critical literature review, analysis of planning documents, open-access statisticaldata, and fieldwork, the article conceptualizes Eisenhüttenstadt’s post-socialist development as amulti-layered and actor-driven transformation rather than a linear decline. Particular attention ispaid to the role of institutional actors at different governance levels, as well as to locally embeddedcultural agents and initiatives that have actively contributed to the reinterpretation of socialist urbanheritage.The findings demonstrate that post-socialist trajectories in monotowns are shaped by theinteraction of strategic instruments – such as privatization regimes, urban restructuring programs,and heritage protection frameworks – and tactical practices, including cultural interventions,adaptive reuse, and network-based local mobilization. Eisenhüttenstadt is discussed as atransformation shaped by deliberate actions of multi-level actors, including state-led restructuringinstruments, municipal planning and housing management, and local cultural initiatives. The caseillustrates how strategic programs and tactical practices interacted in housing demolition, resourcere-concentration, and heritage re-interpretation. Methodologically, the paper reconstructs keyphases through analysis, offering a comparative lens for post-socialist monotowns, includingUkraine.
Keywords: Eisenhüttenstadt; mono-industrial town; shrinking city; postsocialist transformations; urban heritage; revitalization